EFFECTS OF FENUGREEK (TRIGONELLA FOENUM-GRAECUM) SEEDS EXTRACT ON THE TESTOSTERONE LEVELS IN RABBITS. : J Peop Univ Med Health Sci. 2025:15(2), 233-244.http://doi.org/10.46536/jpumhs/2025/15.02.646 - Nargis Pirya1, Ghulam Mustafa Dahri2, Muhammad Azhar Mughal3, Farzana Memon4, Zaheera Yousif5, Ayesha Asad Memon5, Muhammad Zain ul Abdeen7, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
Background: Fenugreek (Trigonella foenum-graecum L.) seeds have been known for its therapeutic properties, particularly its influence on male reproductive hormones. Despite extensive data from rodent and human models, limited studies have investigated its androgenic potential in lagomorphs, particularly rabbits, which share notable physiological homology with humans in steroidogenesis. Objective: To evaluate the dose-dependent effects of fenugreek seeds extract on serum testosterone levels in healthy adult male rabbits under controlled experimental conditions. Methods: A randomized controlled animal study was conducted using thirty adult male rabbits (aged 16-24 months), assigned into three groups, in each group (n=10). Group-A labeled as control, while Group B and Group-C have received fenugreek seed extract at 500 mg/kg and 1000 mg/kg bodyweight, respectively, orally for 45 days. Blood samples were collected at Day 0, Day 23, and Day 45, and serum testosterone levels were analyzed using standard biochemical assays. Statistical comparisons were made by using SPSS version 25.0, ANOVA test, where p<0.05 was considered as significant. Results: Testosterone levels remained stable in the control group (Group-A) across all time points (p>0.05). Group-B exhibited a statistically significant increase from 27.77 ± 3.27 ng/dl at baseline to 29.77 ± 3.67 ng/dl at Day 45 (p=0.01), while Group-C demonstrated a comparable elevation from 26.86 ± 3.67 ng/dl to 29.11 ± 3.83 ng/dl (p=0.001). The dose-dependent response was evident, with both treated groups showing sustained testosterone elevation. No major adverse events were noted except for mild lethargy in one subject from Group-B. Conclusion: Fenugreek seed powder extracts significantly enhanced serum testosterone levels in rabbits in a dose-dependent manner without adverse effects, highlighting its potential as a natural androgenic agent. These findings support its translational relevance and warrant further exploration in human clinical trials.